Inverse association between dietary fiber intake and gallstone disease in U.S. adults: a cross-sectional study from the NHANES database - Dianbao Zuo; Dianbao Zuo; Ming Sang; Xiaodong Sun; Guoping Chen; Kangkang Ji; Kangkang Ji (Frontiers in Nutrition)
BackgroundThe cross-sectional association of dietary fiber intake with gallstone disease in United States adults remains to be comprehensively elucidated.MethodsWe used the National Health and Nutrition Examination Survey (NHANES) data from 2017–2023. The assessment of dietary fiber intake was derived from 24-h dietary recalls. Stratified analyses were then used to demonstrate dietary fiber intake corresponding to different groups of gallstone and non-gallstone conditions. The use of weighted logistic regression was employed to explore the correlation between dietary fiber intake and gallstone disease. Subgroup and interaction analyses were used to identify potential interacting factors. Additionally, restricted cubic spline was used to assess the dose–response between dietary fiber and gallstone risk.ResultsThe study population comprised 9,273 patients, with a gallstone prevalence of 10.47% (971 cases). In the context of various subgroups, patients diagnosed with gallstones exhibited a reduced dietary fiber intake in comparison with individuals not bearing gallstones. In the fully adjusted model, an inverse association was observed between dietary fiber intake and gallstone disease (odds ratio (OR), 95% confidence interval (CI); 0.98 (0.96,1.00), p value = 0.039). The highest quartile of dietary fiber intake exhibited a lower risk of gallstone disease in comparison with the lowest quartile (quartile 4 vs. quartile 1: 0.65 (0.45, 0.94), p value = 0.022). The inverse correlation between dietary fiber intake and the prevalence of gallstones was found to be statistically significant in several subgroups, including males, Hispanic individuals, those with less than a high school education, alcohol consumers, and individuals diagnosed with diabetes. Furthermore, the analysis of dose–response curves indicated a nearly linear correlation between dietary fiber intake and the risk of gallstone development.ConclusionDietary fiber intake is inversely associated with gallstone disease in United States adults. Adequate dietary fiber intake may be beneficial in reducing gallstone prevalence.